Peran Media Sosial dalam Kekerasan Seksual : Tanggapan Mahasiswa USU Terhadap Kasus Fantasi Sedarah - Hairani Siregar; Lucky Masro Purba; Davrilla Giani Sitepu; Exanty Br Pinem (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study emphasizes how social media can build public opinion on the case of "Incest Fantasy," which had become a hot topic in the public. By looking at the viewpoint of undergraduate from the University of North Sumatra (USU) as informants, this study focus to examine how students respond to the case of "incest fantasy" and how they view the part of social media in spreading and connecting issues of sexual violence against children. This examination uses a descriptive qualitative detain with interview techniques. From the interview results, it can be discern that most students understand that social media can be an effectual tool for expressing criticism also raising awareness, but on the other hand, it can also have a harmful if used without supervision and good literacy. Therefore, it is major for social media users to be more aware also critical of the impact of the content they share or consume, additionally the importance of rules that support the defense of human values.